Analysis of the Transcriptional Control of Bcl11b in Chicken: IRF1 and GATA1 as Negative Regulators - Lingling Qiu; Haojie Wang; Wenhao Li; Ting Yang; Hao Bai; Guobin Chang (Animals)
B-cell lymphoma/leukemia 11B (Bcl11b) plays roles in cell proliferation and apoptosis and holds a pivotal position within the immune system. Our previous studies have demonstrated that Bcl11b can promote cell apoptosis to curb ALV-J infection. To gain insights into the molecular mechanisms underlying Bcl11b expression regulation in chickens, we constructed various truncated dual luciferase reporter vectors and analyzed the promoter region of Bcl11b. We employed promoter-binding TF profiling assay and the dual luciferase assay of site-directed mutagenesis and the expression level of interfering or overexpressing transcription factors were used to study their transcriptional regulation mechanism of chicken Bcl11b and functions in ALV-J infection. Our findings revealed core regulatory regions of the chicken Bcl11b promoter. By examining the −606~−363 bp region, we identified several transcription factors and their binding sites. Mutational and functional analysis further revealed interferon regulatory factor-1 (IRF1) and GATA-binding protein 1 (GATA1) as critical factors for the repression of chicken Bcl11b, thereby affecting cell apoptosis and ALV-J replication. Furthermore, DNA methylation analysis indicated that methylation may also contribute to changes in Bcl11b promoter activity. These findings offer valuable insights into the regulatory mechanisms of chicken Bcl11b and provide promising targets for molecular breeding and genetic improvement of disease resistance in chickens.